Corrosion-induced microstructure degradation of copper in sulfide-containing simulated anoxic groundwater studied by synchrotron high-energy X-ray diffraction and ab-initio density functional theory calculation. (15th May 2021) - Zhang, Fan; Örnek, Cem; Liu, Min; Müller, Timo; Lienert, Ulrich; Ratia-Hanby, Vilma; Carpén, Leena; Isotahdon, Elisa; Pan, Jinshan
Highlights: Synchrotron high-energy XRD and DFT calculation were used to study degradation of Cu exposed to S-containing groundwater. XRD revealed heterogeneous lattice deformation and lattice expansion in near-surface regions after two-month exposure. DFT calculations suggest spontaneous adsorption of H, H_S and H_S_H on Cu surface, and S promotes H adsorption on Cu. Water causes surface reconstruction and promotes H insertion, occurring via interstitial sites next to vacancies leading to lattice dilation and metal bond weakening. H infusion in the presence of S caused lattice degradation, indicating a risk for H-induced corrosion cracking. Abstract: Synchrotron high-energy XRD measurements and ab-initio DFT calculations were employed to investigate microstructural degradation of copper upon exposure to sulfide-containing anoxic groundwater simulating nuclear waste repository. After two-month exposure, the high-energy XRD measurements revealed heterogeneous lattice deformation in the microstructure and lattice expansion in near-surface regions. The DFT calculations show that sulfur promotes hydrogen adsorption on copper. Water causes surface reconstruction and promotes hydrogen insertion into the microstructure, occurring via interstitial sites next to vacancies leading to lattice dilation and metal bond weakening. Hydrogen infusion in the presence of sulfur caused lattice degradation, indicating a risk for H-induced cracking.